The Impact of Ability, Work Motivatedness, Organizational Commitment and Work Environment on Employee Performance - Yusran; Abdul Hadi Sirat; Benny Agus; Lisda Ariani Simabur (Jurnal Manajemen Bisnis, 2021)
This study aims to find out and analyze the influence of ability, work motivation, organizational commitment and work environment to the performance of police personnel Research respondents are ternate police personnel numbering 80 people. The analysis method used is Multiple linear regression. The results showed that simultaneously the ability, motivation of work, organizational commitment and work environment significantly affect the performance of Ternate police personnel. Partial capabilities (X1) and organizational commitment (X3) have a positive and significant effect on personnel performance (Y). Meanwhile, work motivation (X2) and Lingkungan_Kerja (X4) had no significant effect on the performance of Ternate Police personnel. Of the four variables studied, the most dominant effect on the performance of police personnel is organizational commitment.